BS ISO 11119-1. Gas cylinders. Refillable composite gas cylinders and tubes. Design, construction and testing. Part 1. Hoop wrapped fibre reinforced composite gas cylinders and tubes up to 450 l (21st August 2019) - British Standards Institution,
No abstract available